2017
DOI: 10.1111/cch.12524
|View full text |Cite
|
Sign up to set email alerts
|

The variation in quality and content of patient‐focused health information on the Internet for otitis media

Abstract: The content and quality of health information for otitis media in parent-and-patient-focused websites is highly variable. Although easy-to-read, high-quality websites with complete content are available, the average website sites is difficult to read without a high school education and is difficult to use. Consideration should be given to adopting a standard approach for presenting disease-specific information to parents and patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…As 1 point is allocated for each of the criteria met, scores range from 0 to 4; a higher score indicates better quality. Although these benchmarks have been applied to evaluate the quality of website-derived health information on various diseases [19-21], the quality of IBD-related information on websites has not yet been reported.…”
Section: Methodsmentioning
confidence: 99%
“…As 1 point is allocated for each of the criteria met, scores range from 0 to 4; a higher score indicates better quality. Although these benchmarks have been applied to evaluate the quality of website-derived health information on various diseases [19-21], the quality of IBD-related information on websites has not yet been reported.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have evaluated the quality of health information websites and found varied results depending on the topic being researched 9–12. However, the literature evaluating how well VAs find and interpret online health information is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are not surprising when compared to similar studies on other healthrelated topics, which have identified similar problems. Joury et al showed with their study of websites showing information for patients with otitis media that there is also a lack of high-quality websites in this field, and only very few pages were written in a language that is accessible to a patient [30]. Johnson et al reported in 2019 that online sources of information for patients with lymphoedema were only suitable for readers with a higher level of understanding, but were unsuitable and misleading for the general population [31].…”
Section: Discussionmentioning
confidence: 99%